The stakeholder corporation : - Wheeler, David (Pitman, 1997)
The Stakeholder Corporation examines the business case for good corporate citizenship, giving you a workable management system for auditing and transforming your stakeholder relationships. At a time when many are talking about the stakeholder economy, this book provides numerous case studies of successful businesses, which demonstrate that stakeholder inclusion is both practical and good for business. Read this book. Improve the lives of your stakeholders. See your business prosper.